Anti windup implementation on different PID structures - Taip, Farah Saleena; Tham, Ming T. (Universiti Putra Malaysia Press, 2008)
Although there have been tremendous advances in control theory over the last 25 years, the PID controller remains very popular and is still widely used in industry. A vital aspect of its implementation is the selection of a suitable set of parameters, as an improperly tuned controller might lead to adverse effects on process operation and worse, cause system instability. In industry, there are various types of PID controllers in addition to the 'textbook' PID but most tuning methods were developed based on this ideal algorithm. Another issue that is always associated with PID controllers is integral windup and the most popular method to overcome this problem is to add an anti windup compensator. This article includes the assessment of three anti windup strategies in combination with different tuning methods. The characteristics of PID controllers tuned using these approaches are evaluated by application to simulated FOPTD processes with different time-delay to time-constant ratios. Different measures were used to assess their performance and robustness properties, and the applicability of the tuning relationships to more typical (non-ideal) PID controllers is also considered. In general, the anti windup compensators successfully reduced the degradation effect caused by integral windup. It was found that the effectiveness of the different anti windup schemes varied depending on controller tuning methods and controller structures.